Plasma neutrophil gelatinase-associated lipocalin as a single test rule out biomarker for acute kidney injury: A cross-sectional study in patients admitted to the emergency department - Vicky Jenny Rebecka Wetterstrand; Martin Schultz; Thomas Kallemose; André Torre; Jesper Juul Larsen; Lennart Friis-Hansen; Lisbet Brandi (PLoS ONE, 2025)
Objectives Acute kidney injury (AKI) is a syndrome with high mortality and morbidity in part due to delayed recognition based on changes in creatinine. A marker for AKI based on a single measurement is needed and therefore the performance of a single measurement of plasma neutrophil gelatinase-associated lipocalin (pNGAL) to predict AKI in patients admitted to the emergency department was tested. Methods Samples from the Triage study which included 6005 consecutive adult patients admitted to the emergency department were tested for pNGAL. The optimal cutoff for pNGAL was determined by the AUC and compared to AKI based on creatinine using different estimations of the premorbid kidney function. Results In 4833 patients, two or more plasma creatinine (pCr) measurements were available allowing the detection of AKI. The highest prevalence of AKI (10%) was found when defining AKI as an increase in pCr ≥26.5 μmol/L from the prior year’s mean pCr. At these conditions the AUC for pNGAL to predict AKI was 85% giving an optimal cutoff of 142.5 ng/mL with a negative predictive value of 0.96, a positive predictive value of 0.35, a specificity of 0.87 and a sensitivity of 0.70. Conclusion The study illustrates that the value of a single measurement of pNGAL is primarily in excluding AKI whereas it`s poorer in predicting the presence of AKI. When diagnosing AKI with pCr the optimal baseline pCr level is the mean of available pCr (mb-pCr) measurements from up to a year prior to the current event.